Melaleuca Snout Beetle, Melaleuca Weevil (unofficial common names), Oxyops vitiosa (Pascoe) (Insecta: Coleoptera: Curculionidae) - James P. Cuda; Susan A. Wineriter; Gary R. Buckingham; Ted D. Center; Kenneth T. Gioeli (EDIS)
Melaleuca, Melaleuca quinquenervia (Cav.) S.T. Blake (Myrtaceae), is an invasive woody plant that is native to Australia, New Guinea, and the Soloman Islands. Melaleuca, also known as the paper bark tree, cajeput, punk tree, or white bottlebrush tree, was introduced into Florida in the late 19th century but apparently failed to naturalize until 1906. It was planted extensively as an ornamental, and eventually invaded suitable forested and non-forested wetland habitats in south Florida forming dense monocultures. This document is EENY-211 (originally published as DPI Entomology Circular 410- updated for this publication), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2003. Revised: July 2004.